Gambaran Perilaku Non-Suicidal Self-Injury (NSSI) Pada Remaja Dengan Kecenderungan Eating Disorders - Fadlulla Zain, Zuhra; Kartika Amelia Arbi, Dian (Jurnal Syntax Fusion, 2023)
This research aims to determine the description of Non-suicidal Self-Injury in adolescents with a predisposition eating disorders. Eating disorders is a persistent pattern of eating disorder that results in changes in the consumption or absorption of food, and that significantly impairs physical health or psychosocial functioning (American Psychiatric Association, 1998). Including Pica, rumination disorder, avoidant/restrictive food intake disorder, anorexia disorder, bulimia nervosa, and binge eating disorder. Non-suicidal self-injury behavior or NSSI defined as behavior that refers to the direct and intentional destruction of body tissue from a person without any intention to end life (Nock, 2010). Including cutting behavior, burning oneself, putting things under the skin, hitting, and biting (Nock, 2010). The subjects in this study were adolescents with an age range of 12-21 years (Monks, 2008). The total subjects in this study were 104 people. The measuring instrument for the NSSI behavior used in this study is Inventory of Statements About Self-Injury (ISAS) compiled by Klonsky and Glenn (2009). The measuring instrument for cut-off eating disorders use a Eating Disorder Examination – Questionnaire (EDE-Q) compiled by Fairburn & Beglin, (2008). Data analysis was performed using descriptive analysis. The results showed that the onset of NSSI behavior was mostly found at the age of 13 years. Then, the most frequently used NSSI behavior methods by adolescents were severe scratching (n = 84, 80.7%), biting (n = 76, 73%), and banging or hitting themselves (n = 76, 73%). As well, it is known that intrapersonal functions is the function most performed by the participants (affect-regulation, self-punishment, and marking distress).